2020
DOI: 10.1084/jem.20200318
|View full text |Cite
|
Sign up to set email alerts
|

Liver X receptors are required for thymic resilience and T cell output

Abstract: The thymus is a primary lymphoid organ necessary for optimal T cell development. Here, we show that liver X receptors (LXRs)—a class of nuclear receptors and transcription factors with diverse functions in metabolism and immunity—critically contribute to thymic integrity and function. LXRαβ-deficient mice develop a fatty, rapidly involuting thymus and acquire a shrunken and prematurely immunoinhibitory peripheral T cell repertoire. LXRαβ’s functions are cell specific, and the resulting phenotypes are mutually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 46 publications
4
30
0
Order By: Relevance
“…Complementarily, the study by Michaels et al (2020) demonstrates that LXRβ not only regulates thymocyte development, but also effector functions of mature T cells. Specifically, they investigated T cell phenotypes using a CD4-Cre LXRβ knockout mouse model and observed, similar to the study by Chan et al (2020), T cell lymphopenia, decreased proliferative capacity, and also spontaneous T cell activation. Using elegant experiments with bone marrow chimeric mice harboring mixed wild-type and LXRdeficient T cells, the authors found that LXRβ is cell-intrinsically required for T cell fitness and effector T cell (T EFF ) development, and that spontaneous T cell activation may derive from deficient regulatory T (T reg) cell functions.…”
mentioning
confidence: 62%
See 3 more Smart Citations
“…Complementarily, the study by Michaels et al (2020) demonstrates that LXRβ not only regulates thymocyte development, but also effector functions of mature T cells. Specifically, they investigated T cell phenotypes using a CD4-Cre LXRβ knockout mouse model and observed, similar to the study by Chan et al (2020), T cell lymphopenia, decreased proliferative capacity, and also spontaneous T cell activation. Using elegant experiments with bone marrow chimeric mice harboring mixed wild-type and LXRdeficient T cells, the authors found that LXRβ is cell-intrinsically required for T cell fitness and effector T cell (T EFF ) development, and that spontaneous T cell activation may derive from deficient regulatory T (T reg) cell functions.…”
mentioning
confidence: 62%
“…Together, the present studies indicate that cell type-specific differential LXR expression and function are likely directly linked to cell type-distinct responses toward LXR deletion or ligand-induced increased activity. These observations, as described by Chan et al (2020) and together with the fact that different NRs are able to cooperate, point out that LXR-mediated actions have to be carefully interpreted when effects cannot be related to specific cellular events. This represents another crucial Cell type-distinct functions of LXRs (LXRα/β) in the regulation of T cell development and function in the thymus and periphery.…”
Section: Insights From Truongmentioning
confidence: 77%
See 2 more Smart Citations
“…A recent report by Chan et al . shows that LXRα and LXRβ are involved in thymic T cell development through mechanisms of action on multiple cell types, including TECs and thymocytes 47 . Developmental stages of iNKT cells are partly overlapped with those of conventional T cells but are distinct such as in NK1.1 expression 3 .…”
Section: Discussionmentioning
confidence: 99%